Cytosolic GDH1 degradation restricts protein synthesis to sustain tumor cell survival following amino acid deprivation. (20th December 2021) - Shao, Jialiang; Shi, Tiezhu; Yu, Hua; Ding, Yufeng; Li, Liping; Wang, Xiang; Wang, Xiongjun
Abstract :